Profesionalisme Guru PAI dalam Pembelajaran Abad 21: Tantangan dan Solusi - Muhammad Dandi Saputro Dandy; Fajar Agung Prayoga; Salsabila Arum Az Zahro Putri (TADARUS, 2026)
The 21st century demands significant transformations across various domains, including education. As key agents in shaping students' character and Islamic values, Islamic Religious Education (PAI) teachers face the complex challenge of harmonizing traditional principles with the demands of modern competencies such as critical thinking, creativity, collaboration, communication, and digital literacy. This research seeks to analyze these challenges and propose relevant solutions. Utilizing a descriptive-analytic qualitative literature review method, the study identifies several key challenges: (1) the gap between pedagogical and technological competencies, (2) high teaching workloads, (3) evolving socio-cultural dynamics of students, (4) limited digital literacy, and (5) the pressure to integrate Islamic values with advancements in science and technology. The corresponding solutions proposed include: (1) enhancing technology-based Continuous Professional Development (CPD) programs; (2) establishing PAI teacher communities of practice; (3) integrating the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach with Islamic values; (4) leveraging digital platforms for interactive learning; and (5) strengthening the teacher’s role as an adaptive facilitator and role model. In conclusion, advancing the professionalism of PAI teachers in the modern era requires a synergistic effort involving individual competency development, institutional policy support, and the reinforcement of a globally competitive, value-oriented educational ecosystem.